Web Service Accounting System - Murad Sulaiman; Mohammad Masoud (My University, 2009)
A web service accounting system is like any accounting system application but instead of saving the information in a local database the company actually get to save it at a server database with the space the company needs providing security for transacting the information.We called our project customized web service accounting system , because the company can choose things like: disk space required, the time the company needs every day, the number of users allowed to use the account and the interface of there own page.The project provides accounting services and reports for companies i.e. the essential accounting services.The required steps of the company to start using AccounTech are simply signing up by creating new company, paying the money through Pay Pal, choosing disk space and time required, uploading companys logo and choosing a theme and inserting the company users that allowed to access companys information. Once the company fulfilled these steps they are   ready to use AccounTechs services.

A web service accounting system is like any accounting system application but instead of saving the information in a local database the company actually get to save it at a server database with the space the company needs providing security for transacting the information.We called our project customized web service accounting system , because the company can choose things like: disk space required, the time the company needs every day, the number of users allowed to use the account and the interface of there own page.The project provides accounting services and reports for companies i.e. the essential accounting services.The required steps of the company to start using AccounTech are simply signing up by creating new company, paying the money through Pay Pal, choosing disk space and time required, uploading companys logo and choosing a theme and inserting the company users that allowed to access companys information. Once the company fulfilled these steps they are   ready to use AccounTechs services.
Web Service Accounting System